Supplementation of vitamin E or a botanical extract as antioxidants to improve growth performance and health of growing pigs housed under thermoneutral or heat-stressed conditions - Ysenia V. Silva-Guillen; Consuelo Arellano; Jeffrey Wiegert; R. Dean Boyd; Gabriela E. Martínez; Eric van Heugten (Journal of Animal Science and Biotechnology, 2024)
Abstract Background Heat stress has severe negative consequences on performance and health of pigs, leading to significant economic losses. The objective of this study was to investigate the effects of supplemental vitamin E and a botanical extract in feed or drinking water on growth performance, intestinal health, and oxidative and immune status in growing pigs housed under heat stress conditions. Methods Duplicate experiments were conducted, each using 64 crossbred pigs with an initial body weight of 50.7 ± 3.8 and 43.9 ± 3.6 kg and age of 13-week and 12-week, respectively. Pigs (n = 128) were housed individually and assigned within weight blocks and sex to a 2 × 4 factorial arrangement consisting of 2 environments (thermo-neutral (21.2 °C) or heat-stressed (30.9 °C)) and 4 supplementation treatments (control diet; control + 100 IU/L of D-α-tocopherol in water; control + 200 IU/kg of DL-α-tocopheryl-acetate in feed; or control + 400 mg/kg of a botanical extract in feed). Results Heat stress for 28 d reduced (P ≤ 0.001) final body weight, average daily gain, and average daily feed intake (−7.4 kg, −26.7%, and −25.4%, respectively) but no effects of supplementation were detected (P > 0.05). Serum vitamin E increased (P < 0.001) with vitamin E supplementation in water and in feed (1.64 vs. 3.59 and 1.64 vs. 3.24), but not for the botanical extract (1.64 vs. 1.67 mg/kg) and was greater when supplemented in water vs. feed (P = 0.002). Liver vitamin E increased (P < 0.001) with vitamin E supplementations in water (3.9 vs. 31.8) and feed (3.9 vs. 18.0), but not with the botanical extract (3.9 vs. 4.9 mg/kg). Serum malondialdehyde was reduced with heat stress on d 2, but increased on d 28 (interaction, P < 0.001), and was greater (P < 0.05) for antioxidant supplementation compared to control. Cellular proliferation was reduced (P = 0.037) in the jejunum under heat stress, but increased in the ileum when vitamin E was supplemented in feed and water under heat stress (interaction, P = 0.04). Tumor necrosis factor-α in jejunum and ileum mucosa decreased by heat stress (P < 0.05) and was reduced by vitamin E supplementations under heat stress (interaction, P < 0.001). Conclusions The addition of the antioxidants in feed or in drinking water did not alleviate the negative impact of heat stress on feed intake and growth rate of growing pigs.